Perfil de mulheres hipertensas crônicas ao engravidar - Bauer, Renato Jose [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Introdução:A hipertensão arterial crônica (HAC) cons:tui enorme desafio de saúde para todas as populações, especialmente nos países de baixa e média renda. Entre as gestantes, es:ma-se uma prevalência entre 6% e 8% das gestações. Um dos Obje:vos do Desenvolvimento Sustentável (ODS) da Organização das Nações Unidas é reduzir a razão de morte materna (RMM) em todo mundo. No Brasil a causa direta de morte materna mais frequente é a hipertensão arterial, em especial pela manifestação em forma de pré-eclâmpsia (PE), a:ngindo a taxa em 2019 de 20%. A gravidez planejada é um marcador de boa qualidade de saúde pública e educacional de uma população. Esse planejamento pode diminuir riscos de desfechos adversos maternos e fetais, pois, ao realizar mudanças de es:lo de vida prévias a gestação, como ingesta com baixo teor de sódio, cessar tabagismo, iniciar a:vidade qsica, adequar o peso materno, adequar o an:-hipertensivo apropriado à gestação reduz-se o risco de inúmeros agravos. Uma complicação grave da HAC é a sobreposição de PE, que ocorre em 13% a 40% dos casos. Para a prevenção da PE as intervenções atualmente reconhecidas que podem resultar em redução do risco incluem o uso de ácido ace:lsalicílico (AAS) e a suplementação de cálcio. ObjeRvos:Determinar o perfil de mulheres portadoras de HAC ao engravidar, iden:ficando-se suas caracterís:cas demográficas, de es:lo de vida e relacionadas à hipertensão arterial e obstétricas. Sujeitos e métodos:Foi realizado estudo prospec:vo e descri:vo com população de mulheres portadoras de HAC, que foram referenciadas aos serviços de assistência pré-natal de risco da Pon:qcia Universidade Católica de São Paulo (PUC-SP) - realizado no Conjunto Hospitalar de Sorocaba (CHS-PUC-SP) e do Hospital das Clínicas da Faculdade de Medicina de Botucatu – Unesp (HC-FMB-Unesp), antes da 20a semana de gestação.Nessa população foram determinadas suas caracterís:cas demográficas e de es:lo de vida, caracterís:cas da hipertensão arterial crônica e caracterís:cas obstétricas Foram excluídas mulheres em que o protocolo do estudo não esteve preenchido com ao menos 90% dos dados. Todas as mulheres incluídas no estudo receberam informações sobre o mesmo e concordando em par:cipar assinaram o termo de consen:mento livre e esclarecido.Os dados ob:dos foram inseridos em planilha de Excel e analisados de forma descri:va através de número e percentagem. A comparação entre os grupos foi feita pelo teste do qui-quadrado (χ2), com significância de p < 0,05.

Introduction: Chronic hypertension (CH) is an enormous health challenge for all populations, especially in low- and middle-income countries. Among pregnant women, a prevalence of between 6% and 8% of pregnancies is estimated. One of the United Na- tions Sustainable Development Goals (SDGs) is to reduce the maternal mortality rate (MMR) worldwide. In Brazil, the most frequent direct cause of maternal death is arterial hypertension, especially in the form of preeclampsia (PE), reaching a rate of 20% in 2019. Planned pregnancy is a good quality marker of public health and education in a population. This planning can reduce the risk of adverse maternal and fetal outcomes, by making lifestyle changes prior to pregnancy, such as low-sodium intake, quitting smoking, starting physical activity, adjusting maternal weight, adjusting antihypertensive drugs appropriate for pregnancy, the risk of numerous diseases is reduced. A serious complication of CH is PE overlap, which occurs in 13% to 40% of cases. For the preven- tion of PE, currently recognized interventions that may result in risk reduction include the use of acetylsalicylic acid (ASA) and calcium supplementation. Objectives: To determine the profile of women with CH when they become pregnant, identifying their demographic characteristics, lifestyle and related to arterial and obstetric hypertension. Subjects and methods: A prospective and descriptive study was carried out with a population of women with chronic hypertension, who were referred to the prenatal care services of the Pontifical Catholic University of São Paulo (PUC-SP) and at Hospital das Clínicas of the Faculty of Medicine Botucatu – Unesp, before the 20th week of pregnancy, within one year. Their demographic and lifestyle characteristics, arterial hypertension and obstetric characteristics were determined. All women included in the study received information about it and signed an informed consent form. The data obtained were entered into an Excel spreadsheet and analyzed descriptively by number and percentage. The comparison between groups was performed using the chi-square test (χ2), with a significance of p < 0.05. Results: There was a predominance of the age group between 20 and 35 years (54.7%), white (75.5%), stable union (94.3%), who have 8 activities outside the home (54.7 %) and a BMI of at least 30 (68.0%) pre-pregnancy. There was a low percentage of pregnant women who practice some physical activity (9.4%), no alcohol consumption and low consumption of illicit drugs (1.9%), smoking was present in 7.6% of pregnant women and 32% used a low-sodium diet. Only 5.7% of CH was secondary, with a duration of less than five years (58.5%) but with 18.9% whose duration was greater than 10 years, in 77.4% of cases there was another medical comorbidity. associated. Most pregnant women (60.4%) used antihypertensive drugs before pregnancy. Only 5.7% of the patients had changed their antihypertensive medication before becoming pregnant. At the present time, the majority (79.3%) used methyldopa and 13.3% did not use antihypertensive drugs. There was a predominance of multiparous women (73.6%). The pregnancy was unplanned in 60.4% of cases. The presence of a risk factor, excluding CH, for developing preeclampsia was present in 90.5% of the cases. 35.9% of the cases used ASA before starting high-risk prenatal care, among all those who did not use it (64.1%), an important part (23.5%) arrived at the referral service with gestational age above 16 weeks, therefore, outside the recommended age as ideal for the best prophylactic effect of aspirin to prevent preeclampsia. As for the use of calcium supplementation, only 34.0% used it to prevent preeclampsia.Conclusions: The analysis of the studied population allows us to conclude that: the percentage of unplanned pregnancy is high, there was a delay for the pregnant woman to reach the high-risk service and failure in the process of preventing preeclampsia through the use of ASA and calcium.
Profile of chronic hypertensive women when pregnant
Keywords: Gestação; Hipertensão arterial crônica; Perfil demográfico; Perfil obstétrico; Gravidez; Demografia; Pesquisa